Social Security Disability Insurance: Applications, Awards, and Lifetime Income Flows - Kreider, Brent (Journal of Labor Economics, 1999)
This article provides new evidence about the impact of Social Security Disability Insurance on male labor force participation decisions based on estimates from a structural model of applications, awards, and state‐contingent lifetime income flows. The lifetime framework makes it possible to consider long‐term opportunity costs associated with early labor force withdrawal and the disincentive to applications resulting from the statutory waiting period before benefits may be received. Estimation techniques account for the self‐selected nature of the pool of applicants when predicting the individual‐specific probability of acceptance and the opportunity costs of applying.